1993
DOI: 10.1038/bjc.1993.373
|View full text |Cite
|
Sign up to set email alerts
|

Growth of cultured human glioma tumour cells can be regulated with histamine and histamine antagonists

Abstract: Summary The 50% survival time for low grade astrocytomas is 50 months and for high grade astrocytomas it is 13 months, underlining the need for new therapies. Several reports show that in vivo histamine antagonists cause retardation of tumour growth in some animal models and prolonged survival in cancer patients. Therefore we have tested the growth modulating effects of histamine and histamine antagonists on human glioma cultures.Twelve freshly excised human gliomas were cultured and tested for their in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…This may indicate the dependence of proliferation of these cell lines on stimulation of the H, receptor. Van der Ven et al [20] reported similar findings and suggested that there is a cell line-specific sensitivity to the addition of cimetidine, as this agent did not inhibit prolieration in all cell lines in their study, as indeed it could not in the present study. The authors [20] go further and argue that this observation indicates that cimetidine induces a specific inhibition of proliferation and no non-specific cytotoxic effect.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This may indicate the dependence of proliferation of these cell lines on stimulation of the H, receptor. Van der Ven et al [20] reported similar findings and suggested that there is a cell line-specific sensitivity to the addition of cimetidine, as this agent did not inhibit prolieration in all cell lines in their study, as indeed it could not in the present study. The authors [20] go further and argue that this observation indicates that cimetidine induces a specific inhibition of proliferation and no non-specific cytotoxic effect.…”
Section: Discussionsupporting
confidence: 79%
“…For example, Ucar [19] reported that cimetidine, in combination with other agents, induced remission of melanomas and certain other tumours in humans and in animals. These findings appear to concur with the suggestion of Van der Ven et al [20], that histamine favours in vivo tumour cell prolieration via the H, receptors. This group studied gliomas exclusively rather than non-CNS tumours, but despite this fundamental difference, their studies yielded results comparable with those described above.…”
Section: Introductionsupporting
confidence: 92%
“…Van der Ven and colleagues (99) and Finn and colleagues (100) had previously tested the growth-modulating effects of CIM on glioma cultures derived from human brain tumors. They observed that high dose (1 mM) CIM induced inhibition of in vitro proliferation of gliomas, while lower concentrations (1 μM) were less effective (99,100). We observed that in vitro 0.1-1 μM CIM significantly decreased migration of both U373 and 9L brain tumor cells (21).…”
Section: Cimetidine and Malignant Gliomasmentioning
confidence: 70%
“…histamine; intermediate conductance Ca 2ϩ -activated K ϩ channels; large conductance Ca 2ϩ -activated K ϩ channels; human glioblastoma GL-15 cells SUBSTANTIAL EXPERIMENTAL DATA show that histamine modulates the growth and migration of glial cells lines derived from brain tumors as well as of primary glioma-derived cells (6,28,34). Histamine binds to three types of membrane receptors: H 1 receptors, usually coupled to phospholipase C activation and internal Ca 2ϩ mobilization; H 2 receptors, connected with adenylate cyclase; and H 3 receptors, controlling histamine turnover and release (11,21).…”
mentioning
confidence: 99%